Persepsi Pemuda Tentang Pola Pelayanan Penatua Dalam Meningkatkan Motivasi Beribadah di GKPI Sigompulon Pahae Julu Tahun 2019 - Loriani Juniati Sitompul (IAKN Tarutung, 2020)
The purpose of this research was to determine youth perceptions about the pattern of elder services in increasing motivation to worship young GKPI Sigompulon Pahae Julu. The hypothesis of this research is the Youth Perception of Elder Service Patterns in Improving Worship Motivation at GKPI Sigompulon Pahae Julu 75% than expected, with a research population of 40 people. Data was collected using a closed questionnaire, with a total of 26 items compiled based on indicators and validity and reliability tested. The results of the data analysis show that the Youth Perceptions of Elder Service Patterns in Improving Worship Motivation at GKPI Sigompulon Pahae Julu 75% than expected, this is evidenced by the results of the analysis of both 81.55% and tcount ttable of 5.521 1.684, thus Ho rejected and Ha acceptedKeywords: Elder Service Pattern, Worship Motivation